1998
DOI: 10.1152/ajpgi.1998.275.5.g1209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gastrin on antroduodenal motility: role of intraluminal acidity

Abstract: The effect of gastrin on the migrating motility complex (MMC) was studied in seven healthy subjects. It was hypothesized that a potential effect of gastrin on the MMC may result from intraluminal acidification through increased gastric acid secretion. Therefore, antroduodenal manometry and intraluminal acidity were recorded simultaneously. The effect of gastric acid inhibition, with and without administration of gastrin, on antroduodenal motility and intraluminal acidity was also evaluated and compared with sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
2
16
1
1
Order By: Relevance
“…Early human experiments revealed that gastrin administered intravenously relaxed the proximal stomach and stimulated the antral contraction [44,[48][49][50]. Via these functional modulations, gastrin decreases the proximal pressure force and increases the distal occlusive resistance, thereby delaying gastric emptying.…”
Section: Hypergastrinemiamentioning
confidence: 99%
“…Early human experiments revealed that gastrin administered intravenously relaxed the proximal stomach and stimulated the antral contraction [44,[48][49][50]. Via these functional modulations, gastrin decreases the proximal pressure force and increases the distal occlusive resistance, thereby delaying gastric emptying.…”
Section: Hypergastrinemiamentioning
confidence: 99%
“…Infusion of gastrin had no effect on duodenal MMC (Zabielski et al 2004). In human subjects, Verkijk et al (1998) studied the effect of gastrin on the small-intestinal MMC using antroduodenal manometry simultaneous with intraluminal acidity recording. Continuous infusion of gastrin-17 (20 pmol/kg) increased intragastric and intraduodenal acidity and suppressed phase II and phase III motor activity in both antrum and duodenum.…”
Section: Local Effects Of Cholecystokinin and Gastrin In The Gutmentioning
confidence: 99%
“…From these results we can conclude that duodenal acidification causes relaxation of the proximal stomach. Previous studies in humans have shown the importance of duodenal pH in the regulation of interdigestive gastrointestinal motility 22 –28 . Duodenal acidification inhibits gastric activity by decreasing the antral phase III occurrence rate, while alkalization of the duodenum increases antral phase III occurrence rate 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Duodenal acidification inhibits gastric activity by decreasing the antral phase III occurrence rate, while alkalization of the duodenum increases antral phase III occurrence rate 22 . 25 –27 Recently we have shown that continuous gastrin‐17 infusion suppresses phase II and phase III motor activity in both antrum and duodenum, while during concomitant gastric acid inhibition the effect of gastrin on the MMC is completely antagonized 28 . It is not exactly known how acid in the duodenum elicits its ‘feedback control’ on gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%